Wound Healing and Pharmacological Evaluation of Mallotus Philippinensis: The Healing Potential of Mallotus Philippinensis Fruit Extract in Rat Models (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Mallotus philippinensis Muell. Arg (MP, Euphorbiaceae) In tropical and subtropical parts ofthe outer Himalayas, is a widely spread perennial shrub or small tree. Since then, a variety of medicalbenefits of Mallotus philippinensis have been shown. The purpose of the current investigation was toascertain if fruit extract has the ability to heal wounds in rat models.